LITERATURE STUDY OF FREE APPLICATIONS OF THE ISLAMIC ECONOMY IN THE PLAY STORE - Furqonul Haq; Sudirman; M. Zaenal Abid; Izzah Khoirunnisa Mudzakir; Laela Quthrunnada (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2023)
Every Android phone registered with a Gmail account will usually automatically be installed with the Google Play or Play Store application. Play store is an online store that provides various kinds of applications. Applications can be obtained via download for free or paid. Applications in the play store have many categories, including applications in the Books and Reference category and Education category applications. This study aims to find free Islamic economic applications in the play store. The sample in this study is a free Islamic economics application in the play store category of education and the category of books & references. This research methodology is qualitative research using literature study techniques (documentation) on the play store. The study results show six free Islamic economic applications in the play store. Each application has its advantages and disadvantages. But overall, all of these Islamic economics applications provide short, concise and explicit Islamic economics material.